The effect of sales growth, asset structure, and profitability on debt policy of mining companies in indonesia stock exchange (BEI) - Hendrawan, Antonius Reza; Prabawa, Sri Adji (Institute of Computer Science (IOCS), 2024)
The purpose of this research is to analyze the influence of revenue growth, asset structure, and profitability on debt policy in the mining sector companies listed on the Indonesia Stock Exchange (BEI) from 2017 to 2021. This study utilizes the Sales Growth Rate (SG) to measure sales growth, Total Asset Return (TAR) to measure asset structure, and Net Profit Margin (NPM) to measure profitability. The research sample consists of 11 companies selected from 60 mining companies over a five-year period using purposive sampling method, resulting in a total of 55 observation data. The data analysis method employed in this research is multiple regression analysis using the Eviews program for data processing. The research data is secondary and sourced from the annual financial reports of mining companies listed on the Indonesia Stock Exchange (BEI) for the period 2017-2021. The findings indicate that sales growth does not have a significant impact on debt policy, asset structure positively influences debt policy, and profitability does not have a positive impact on debt policy